The 21st century global digital economies revolution and the aftermath of COVID-19 pandemic: Some anticipated implication changes for developing nations - Fosu, Agyei (UI Scholars Hub, 2020)
The 21st century digital global economies era changed developmental approaches drastically to a point where most researchers, policy makers, and developers have asserted that to achieve economic development for developing nations; it is paramount for Information and Communications Technologies (ICTs) investments in all sectors contributing to their economy. The current COVID-19 pandemic and the various measures taken by governments such as lockdown, curfew, companies asking employees to work from home, and the use of e-learning by schools to curb the disease brings into perspective the assertion raised by various scholars about the need for developing nations to invest in ICTs in order to stimulate economic development. In line with this assertion from various authors, the author of this article believes that the following two questions are critical for planners, policy developers, and agents of change for economic development, especially for developing nations: first, how are the COVID-19 pandemic and the measures such as lockdown, curfew, and isolation taken by various governments and corporate bodies going to fuel the already in motion global wave of the 21st century digital economies revolution propelled by the rapid development in ICTs and its devices? Second, how will ICTs investment and ICTs leverage foster development in economic sectors in developing nations' economies? Thus, this article will look at some anticipated implication changes in terms of ICTs investments and sectors in a developing nation’s economy that will see or need these massive non-negotiable ICTs investments and leveraging of ICTs in order to foster economic growth and development.